Inter-Island Water Crossings by Peary Caribou, South-Central Queen Elizabeth Islands - Miller, Frank L. (ARCTIC, 1995)
Satellite and conventional radio telemetry were used to obtain information on daily and seasonal movements of Peary caribou (Rangifer tarandus pearyi) on south-central Queen Elizabeth Islands, Northwest Territories, Canada. Seventeen Peary caribou were captured in 1993 and fitted with telemetry neck collars. Seven collars housed both a Satellite Platform Transmitter Terminal package and radio telemetry package; the other 10 collars all housed only the radio telemetry package. Three of the collared caribou, along with at least 16 of their companion animals, made inter-island water crossings by swimming between Ile Vanier and Massey or between Massey Island and Ile Marc in August 1993. Of particular note is that two-month-old calves, as well as adult caribou, were involved in some of the frigid saltwater crossings. The water crossing between Ile Vanier and Massey Island required a minimum straight-line swim of 2.5 km and that between Massey Island and Ile Marc a minimum 1.6 km swim, depending on points of entry and exit from the water. That evidence composes the first documented account of Peary caribou swimming between any of the Queen Elizabeth Islands.Key words: Peary caribou, Queen Elizabeth Islands, Northwest Territories, inter-island summertime water crossings, swimming On a utilisé la télémesure par satellite et la télémesure radioélectrique traditionnelle pour obtenir de l'information sur les déplacements quotidiens et saisonniers du caribou de Peary (Rangifer tarandus pearyi) dans la partie centre-sud des îles de la Reine-Élisabeth situées dans les Territoires du Nord-Ouest au Canada. En 1993, on a capturé 17 caribous de Peary qu'on a équipés de colliers émetteurs pour télémesure. Sept de ces colliers contenaient à la fois un ensemble de terminal émetteur à plate-forme satellite et un ensemble de télémesure radioélectrique, le restant des colliers ne contenant que ce dernier. Durant le mois d'août 1993, trois des caribous équipés de colliers accompagnés d'au moins 16 de leurs congénères ont traversé à ...